Lymphoma of the trigeminal nerve – the need for histological diagnosis. (April 2014) - Perera, Chandrashan; Fitt, Gregory; Kalnins, Renate; Lee, Stewart; Gonzalvo, Augusto
Abstract CNS lymphoma involving the trigeminal nerve is a rare condition which presents as a cavernous sinus lesion. It may mimic the radiological appearance of other lesions, and biopsy is essential before considering empirical radiotherapy for lesions in this region. We report the radiological, histopathological and operative findings of a primary non Hodgkin B cell lymphoma involving the trigeminal nerve.